Knowledge and clinical practices of medical doctors regarding nutrition in cirrhosis patients – a multicentre study from Pakistan - Laima Alam; Hafiz Faisal Ali; Mafaza Alam; Jawad Khan; Shaista Khan (Journal of the Pakistan Medical Association, 2021)
Objective: The objective of the study is to determine the nutritional knowledge and clinical practices of medical doctors regarding nutrition in cirrhosis patients in a multicentre study. Methods: This multi-centre cross-sectional knowledge and practice (KAP) study was conducted from January 2020 to March 2020 and comprised of physicians working in wards, Out Patient and Emergency Departments. The participants were interviewed using a self-generated structured questionnaire after adequate literature review. The data was analysed using SPSS 16.0. Results: Of the 92 participants, 52 (56.5%) were males, the mean age of the physicians was 28.3 ± 4 years with mean years in service of 3.7 ± 3 years. The mean score obtained was 5.8 ± 2.1 (out of 13). An alarmingly low percentage (35.9%) of physicians had received formal training, 29.3% were giving regular nutritional counselling and 52.2% wrongly believed in the implementation of restricted diets. Salt, water and lipids/oils were incorrectly considered to be avoided in decompensated patients in the percentages of 61%, 49% and 24%, respectively. Mean knowledge scores varied significantly for physicians dealing with cirrhosis patients on daily basis and those who received formal training. Gender, number of service years and physicians providing counselling on regular basis (without proper training) did not impact the scores significantly. Conclusion: The nutritional knowledge of our medical doctors regarding cirrhosis is sub-optimal, the clinical practices adopted are not evidence based and the clinical assessment with nutritional counselling lack vigour and consistency. Continuous...